Příprava a řízení stavební zakázky z pohledu investora - Bobková, Martina (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Tato diplomové práce se zabývá přípravou a řízením stavební zakázky z pohledu investora. Teoretická část se koncepčně zabývá projektovým řízením, včetně potřebné legislativy. V praktické části je popsána příprava a řízení veřejné zakázky u konkrétního veřejného zadavatele. Výsledkem práce je základní metodický postup řízení projektů veřejným zadavatelem.

This diploma thesis is related to construction order preparation and management from the investor´s view. Theoretical part deals with the project management, essential legislation included. In the practical part the construction order preparation and management of the concrete contracting authority is described. This work´s outcome is the elementary methodical process how to manage project by a contracting authority.
Construction Order Preparation and Management from Aspect of Investor
Keywords: Projekt; veřejný zadavatel; veřejná zakázka; legislativa; smluvní vztahy; financování; dotace; projektová dokumentace; nabídka.; Project; Contracting Autohority; Construction Order; Legislation; Contractual relationship; Financing; Grant; Project Documentation; Offer.